Design and Development of a Field Work Reporting System Application for Metro Interior - Dwi Faza Wardanu Damanik; Zulham Sitorus; Khairul Khairul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to design and build a reporting system application for field workers at Metro Interior, a company specializing in interior design. In its operations, Metro Interior faces challenges in efficiently monitoring and managing field workers' activities, which affects report delays, data accuracy, and suboptimal coordination. The designed application will serve as a solution to these issues by providing a platform that allows field workers to create reports directly from the work site. The main features of this application include real-time reporting, task management, project progress tracking, and data collection related to field activities. The application development methodology involves user needs analysis, system design, software development, and system testing. The application is designed using the latest technology to support both mobile and desktop devices, enhancing accessibility for users both in the field and in the office. The expected outcome of this research is to improve reporting efficiency, data accuracy, and coordination between field workers and management teams at Metro Interior. With the implementation of this application, Metro Interior will be able to better monitor and manage projects, reduce administrative errors, and accelerate data-driven decision-making.